2011
DOI: 10.1016/j.cub.2011.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Resurrecting Extinct Interactions with Extant Substitutes

Abstract: There is increasing evidence that restoration ecologists should be most concerned with restoring species interactions rather than species diversity per se [1]. Rewilding with taxon substitutes, the intentional introduction of exotic species to replace the ecosystem functions of recently extinct species, is one way to reverse ecosystem dysfunction following the loss of species interactions [2]. This is highly controversial [3], in part because of a lack of rigorous scientific studies [4]. Here we present the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 15 publications
1
111
0
1
Order By: Relevance
“…However, even if germination can occur in the absence of suitable dispersers, these are still required to transport the seed away from the parent plant and can thereby enhance germination probability. This was found in the rewilding study by Griffiths et al [25] (see §4). Consequently, resurrecting the interactions between large-bodied seed dispersers and dispersallimited plants is an increasingly important topic for conservation biologists.…”
Section: Links Between Animal Physiology and Disperser Effectivenesssupporting
confidence: 70%
See 3 more Smart Citations
“…However, even if germination can occur in the absence of suitable dispersers, these are still required to transport the seed away from the parent plant and can thereby enhance germination probability. This was found in the rewilding study by Griffiths et al [25] (see §4). Consequently, resurrecting the interactions between large-bodied seed dispersers and dispersallimited plants is an increasingly important topic for conservation biologists.…”
Section: Links Between Animal Physiology and Disperser Effectivenesssupporting
confidence: 70%
“…An interesting case study in this regard is the critically endangered large-fruited ebony Diospyros egrettarum, which is endemic to a 25-ha island off Mauritius (Ile aux Aigrettes). Intensive study of the species from 1986 to 2000 found seedlings to occur only under maternal trees [25]. This situation has been linked to the extinction of endemic Cylindraspis tortoises on Mauritian islands by humans in the mid-nineteenth century (within the lifetime of adult trees present now).…”
Section: Linking Plant Conservation To the Physiology Of Dispersersmentioning
confidence: 99%
See 2 more Smart Citations
“…Conservation practitioners are starting to employ large and giant tortoises (family Testudinidae) in island ecosystems such as the Galapagos, the Mascarenes and the Seychelles to replace extinct tortoises with extant analogues (Hansen et al 2010). This can improve seed germination and establishment of endangered largefruited plant species (Griffiths et al 2011). However, implementation of rewilding projects to restore plant-frugivore interactions on islands is still rare (Kaiser-Bunbury et al 2010), and empirical evidence as well as rigorous scientific studies on trophic rewilding are often lacking (Svenning et al 2016).…”
Section: Implications For Conservation and Restorationmentioning
confidence: 99%